(untitled) (Ciencias Económicas, 2024)
The text addresses the issue of "Assessment by evidence of learning in Mathematics as a Language" and describes how this approach has been implemented in the framework of the CAI+D 2020 project at the Faculty of Economics, UNL. The main objective is to achieve a learning assessment system that makes it possible to assess knowledge and competences throughout the development of the subject "Mathematics as a Language" in order to be able to grant promotion without the need for a final exam. Evidence-based assessment involves using data and empirical evidence to evaluate the effectiveness of educational practices. It seeks to obtain objective information about students’ acquired knowledge, skills, competencies, abilities and levels of achievement. Furthermore, it stresses the importance of conceiving assessment as part of the learning and teaching process, not only as a final grade. The text mentions examples of evidence-based assessment activities, such as multiple-choice, true-false and mathematical problems that are used in written assessments called evidence of learning assessments of different topics in the programme, which are carried out by students during the course of Mathematics as a language. In summary, evidence-based assessment is a useful tool for improving student learning and making informed decisions to improve the quality of teaching in mathematics. The importance of using this approach to evaluate teaching effectiveness and promote student success is also mentioned.